2020
DOI: 10.30629/2618-6667-2020-18-3-42-48
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Changes in Comorbidity Alcohol Dependence and Affective Disorders

Abstract: In this study, we sought to assess the level of cognitive functioning in patients with comorbid alcohol dependence and affective disorder, as well as to compare the detected changes with the indicators of cognitive tests in patients suffering only from alcoholism or affective disorder. It is suggested that patients with comorbidity may have a more severe cognitive deficit than patients with a single diagnosis.Materials and methods. We examined 100 patients aged 30–50 years before treatment: 30 patients with af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…One recent study revealed that patients with comorbid alcohol dependence and affective disorder manifested significant impairments in executive control, working memory, attention and cognitive flexibility compared to healthy individuals, and patients with only alcohol dependence or affective disorder [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent study revealed that patients with comorbid alcohol dependence and affective disorder manifested significant impairments in executive control, working memory, attention and cognitive flexibility compared to healthy individuals, and patients with only alcohol dependence or affective disorder [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…BD patients with AUD show impaired verbal learning and memory [ 21 , 22 ], higher delay discounting [ 23 ], significant memory deficits more specifically the recognition of previously presented information [ 24 ] and, more deficits in executive functioning [ 25 , 26 ]. One study found significant impairments in executive control, working memory, attention and cognitive flexibility in comorbid AUD and BD patients, compared to healthy individuals, and patients with only AUD or BD patients [ 27 ]. On the other hand, BD patients without AUD also show impaired verbal learning and memory [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%